DIGITAL NOMADS: THE WHOLE WORLD AS A GLOBAL OFFICE - VIZJAK, Maja; PERIĆ KASELJ, Marina (Journal of process management and new technologies, 2024)
New technologies and high-speed Internet have enabled great flexibility in work. A digital nomad is simultaneously independent and lives and works in several places! A digital nomad is an entrepreneur or employee who almost exclusively uses digital technologies for his business activity. Croatia has caught up with the global trend of regulating the status of digital nomads and ranks highly in the rankings of destinations desirable for digital nomads. Since January 2021, when the visa program for digital nomads was introduced, a total of 2,560 applications have been received and a total of 1,038 have been approved. Croatia is one of the first EU members to regulate one-year residence and strategically develop the offer of the interesting economic and tourism sector. Digital nomads are excellent potential tourism ambassadors since they often migrate and have rich experience of staying in other countries. In a survey, the majority of respondents confirmed that Croatia is the preferred destination for digital nomads. The aim of this paper is to confirm the potential of digital nomads. The scientific contribution is manifested in the detection of the benefits of the further development of digital nomads as a profession of the future.